Anticancer organorhodium and -iridium complexes with low toxicity in vivo but high potency in vitro: DNA damage, reactive oxygen species formation, and haemolytic activity. Issue 80 (9th September 2019) - Parveen, Shahida; Hanif, Muhammad; Leung, Euphemia; Tong, Kelvin K. H.; Yang, Annie; Astin, Jonathan; De Zoysa, Gayan H.; Steel, Tasha R.; Goodman, David; Movassaghi, Sanam; Söhnel, Tilo; Sarojini, Vijayalekshmi; et al.
Abstract : Dinuclear Rh III (Cp*) and Ir III (Cp*) complexes demonstrated potent in vitro anticancer activity while exhibiting low toxicity in haemolysis studies and in vivo zebrafish models. Abstract : Redox-modulating anticancer drugs allow the exploitation of altered redox biology observed in many cancer cells. We discovered dinuclear Rh III (Cp*) and Ir III (Cp*) complexes that have in vitro anticancer activity superior to cisplatin and the investigational drug IT-139, while being less toxic in haemolysis and in vivo zebrafish models. The mode of action appears to be related to DNA damage and ROS-mediated stress pathways.